(untitled) (Research, Society and Development, 2021)
The kid aggregate in its natural composition can have several properties that can be altered by virtue of the type and quantity of the components involved. To identify such properties, it is necessary to do experiments using specific methods and equipment. Given this context, this work aims to do, analyze in the samples of deposits of aggregates kids to verify the quality of this material. The study will have as a starting point test for the granulometric definition, X-ray flowering (FRX) and king X diffraction (XRD). After the laboratory tests, the respective graph scans will be assembled a graph with results of the XRD assay and the granulometric curves for each sample. Based on the experimental results obtained in accordance with the current standards, the analyses will be carried out. At the conclusion of this article, we intend to define the quality of the three types of aggregates kids is the most suitable for each specialty in construction.